Recovery of Polyphenols from Rose Oil Distillation Wastewater Using Adsorption Resins – A Pilot Study - Rusanov, Krasimir; Garo, Eliane; Rusanova, Mila; Fertig, Orlando; Hamburger, Matthias; Atanassov, Ivan; Butterweck, Veronika (Planta Medica, 2014)
The production of rose oil from rose flowers by water steam distillation leaves a water fraction of the distillate as main part of the waste. Therefore, the rose oil distillation wastewater represents a serious environmental problem due to the high content of polyphenols which are difficult to decompose and have to be considered as biopollutants when discarded into the drainage system and rivers. On the other hand, natural polyphenols are valuable compounds with useful properties as bioactive substances. Until now there is no established practice for processing of rose oil distillation wastewater and utilization of contained substances. Thus, it was the aim of this study to develop a strategy to separate this wastewater into a polyphenol depleted water fraction and a polyphenol enriched fraction which could be developed into innovative value-added products. In a first step, the phytochemical profile of rose oil distillation wastewater was determined. Its HPLC-PDA-MS analysis revealed the presence of flavan-3-ols, flavanones, flavonols and flavones. In a second step, the development of a stepwise concentration of rose oil distillation wastewater was performed. The concentration process includes a filtration process to eliminate suspended solids in the wastewater, followed by adsorption of the contained phenolic compounds onto adsorption resins (XAD and SP). Finally, desorption of the polyphenol fraction from the resin matrix was achieved using ethanol and/or aqueous ethanol. The result of the process was a wastewater low in soluble organic compounds and an enriched polyphenol fraction (RF20 SP-207). The profile of this fraction was similar to that of rose oil distillation wastewater and showed the presence of flavonols such as quercetin and kaempferol glycosides as major metabolites. These compounds were isolated from the enriched polyphenol fraction and their structures confirmed by NMR. In summary, a pilot medium scale system was developed using adsorption resins for the recovery of polyphenols from rose oil distillation wastewater suggesting an industrial scalability of the process.
Keywords: Rosa damascena; Rosaceae; rose oil distillation; wastewater management; adsorption resin; polyphenols